Gambaran Work-Life Integration Pada Full Time Employees - Naila Khansa Almaira; Rafa Akbar Salivian Alkahfi; Agnes Vania Yahya; Valerie Alicia Erica Rumbajan; Daniel Lie (Universitas Muhammadiyah Gresik, 2025)
Background: This study explores the depiction of work-life integration among full-time employees. Changes in organizational culture and technology have blurred the boundaries between work and personal life, requiring employees to manage professional demands while maintaining personal well-being. WLI, which consists of work-to-life and life-to-work dimensions, emphasizes dynamic integration rather than strict separation, potentially enhancing productivity and reducing stress. Objective: The aim of this research is to further understand and explore the depiction of work-life integration (WLI) among full-time employees. Method: A quantitative approach was used with non-probability sampling techniques and purposive sampling methods involving 110 full-time employees as respondents. Results: The findings indicate that the level of work-life integration among full-time employees falls within the moderate category (M = 3.88). The work-to-life dimension shows a higher level of integration (M = 4.19) compared to the life-to-work dimension (M = 3.58). Conclusion: These findings suggest that the integration between work and personal life is at a moderate level, indicating a fairly balanced relationship between the two domains.